2007
DOI: 10.1208/pt0803073
|View full text |Cite
|
Sign up to set email alerts
|

Development and in vitro evaluation of an oral floating matrix tablet formulation of diltiazem hydrochloride

Abstract: The purpose of this research was to prepare a floating drug delivery system of diltiazem hydrochloride (DTZ). Floating matrix tablets of DTZ were developed to prolong gastric residence time and increase its bioavailability. Rapid gastrointestinal transit could result in incomplete drug release from the drug delivery system above the absorption zone leading to diminished efficacy of the administered dose. The tablets were prepared by direct compression technique, using polymers such as hydroxypropylmethylcellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…The formulations containing higher NaHCO 3 ratios -10 % w/w (F6) and 20 % w/w (F7) had significantly shorter floating lag time (1 min) than other formulations. Moreover, a similar conclusion was noted by Gambhire et al (2007) who concluded that as the percentage of NaHCO 3 increases, the floating lag time decreases. This phenomenon might be due to the generation of larger amounts of effervescence with higher NaHCO 3 percentage which led to an increase in the rate of pore formation and consequently rapid hydration of the minitablets' matrices.…”
Section: Influence Of Formulation On the Floating Lag Time And Duratisupporting
confidence: 81%
“…The formulations containing higher NaHCO 3 ratios -10 % w/w (F6) and 20 % w/w (F7) had significantly shorter floating lag time (1 min) than other formulations. Moreover, a similar conclusion was noted by Gambhire et al (2007) who concluded that as the percentage of NaHCO 3 increases, the floating lag time decreases. This phenomenon might be due to the generation of larger amounts of effervescence with higher NaHCO 3 percentage which led to an increase in the rate of pore formation and consequently rapid hydration of the minitablets' matrices.…”
Section: Influence Of Formulation On the Floating Lag Time And Duratisupporting
confidence: 81%
“…The samples were analyzed for drug release by measuring the absorbance at 225 nm spectrophotometrically (UV-1800, Shimadzu, Japan) after suitable dilution. All determinations were performed in triplicate [5][6][7][8].…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%
“…Absorbance of these solutions was measured at 285 nm using a UV/Visible spectrophotometer. The percentage drug release was plotted against time to determine the release profile 14 .…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 99%